Improvement of a Terahertz Detector Performance Using the Terajet Effect in a Mesoscale Dielectric Cube: Proof of Concept. Issue 5 (3rd March 2020) - Minin, Igor V.; Minin, Oleg V.; Delgado-Notario, Juan A.; Calvo-Gallego, Jaime; Velázquez-Pérez, Jesus E.; Ferrando-Bataller, Miguel; Meziani, Yahya Moubarak
Abstract : Herein, a simple terahertz (THz) receiver that uses subwavelength focusing of the THz beam on the detector area is proposed. As a proof of concept, a THz detection system with an original optical coupling scheme is implemented, where the signal to be detected is coupled to a THz detector through a mesoscale dielectric particle lens. Coherent detection is successfully demonstrated with an enhancement of the detector sensitivity of about 4.3 dB, compared with that of a direct detection system with the slight decreasing (≈1.67 times) of noise equivalent power value. The results show that the proposed method can reduce the size and increase the sensitivity of various THz systems, including imaging, sensing, and ranging, which would enable significant progress in different fields such as physics, medicine, biology, astronomy, security, etc. Abstract : A dielectric cube is placed at the length of the terajet in front of a terahertz detector. The enhancement of the detector responsivity by 4.3 dB with the decreasing of noise equivalent power is experimentally demonstrated under excitation of 0.3 THz. This opens the way for the development of new terahertz detectors that could overcome the diffraction limit obstacle.